(untitled) (Spanish Yearbook of International Law, 2011)
This paper analyses Spanish regulation and practice in matters of intercountry adoption. It specifically studies the circumstances and scope of the intervention of Spanish administrative authorities. It likewise addresses the constitution of adoption by Spanish authorities making reference to the criteria of international jurisdiction and applicable law. Finally, it examines the systems, procedures and condition applicable to the recognition of foreign adoptions and post-adoptive circumstances.